Task offloading and resource allocation in NOMA-based ultra-dense MEC networks - Yun SHENG; Chen XU; Guangyuan ZHENG (Dianxin kexue)
In order to improve spectrum efficiency and meet the service demands of massive users, a non-orthogonal multiple access (NOMA)-based ultra-dense mobile edge computing (MEC) system was considered.In order to solve the serious communication interference caused by simultaneous offloading of multiple users and make efficient use of edge server resources, a joint task offloading and resource allocation scheme was proposed to minimize the system energy consumption while meeting the quality of service (QoS) of all users.Offloading decision, power control, computation resource and subchannel resource allocation were jointly considered in the proposed scheme.Simulations results show that the proposed scheme can efficiently lower system energy consumption compared to the other offloading schemes.